Narrative Review of Hyperferritinemia, Iron Deficiency, and the Challenges of Managing Anemia in Aboriginal and Torres Strait Islander Australians With CKD - Majoni, Sandawana William (Kidney Int Rep, 2020)
Aboriginal and Torres Strait Islander Australians (Indigenous Australians) suffer some of the highest rates of chronic kidney disease (CKD) in the world. Among Indigenous Australians in remote areas of the Northern Territory, prevalence rates for renal replacement therapy (RRT) are up to 30 times higher than national prevalence. Anemia among patients with CKD is a common complication. Iron deficiency is one of the major causes. Iron deficiency is also one of the key causes of poor response to the mainstay of anemia therapy with erythropoiesis-stimulating agents (ESAs). Therefore, the effective management of anemia in people with CKD is largely dependent on effective identification and correction of iron deficiency. The current identification of iron deficiency in routine clinical practice is dependent on 2 surrogate markers of iron status: serum ferritin concentration and transferrin saturation (TSAT). However, questions exist regarding the use of serum ferritin concentration in people with CKD because it is an acute-phase reactant that can be raised in the context of acute and chronic inflammation. Serum ferritin concentration among Indigenous Australians receiving RRT is often markedly elevated and falls outside reference ranges within most national and international guidelines for iron therapy for people with CKD. This review explores published data on the challenges of managing anemia in Indigenous people with CKD and the need for future research on the efficacy and safety of treatment of anemia of CKD in patients with high ferritin and evidence iron deficiency.